KEBERHASILAN KADER PEMBANGUNAN DESA (KPD): MOTIVASI BIROKRATIK DAN REALITA PEMBANGUNAN> Success of Village Development Cadre (KPD) Bureaucratic Motivatuion and Developmeent Reality. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACTThe aims of this research are: (a) to describe and to explain the implementation role of KPD (Village Development Cadre) in the Regency of Barru, (b) to identify and explain the factors that influence the KPD role in the village development, and (c) to develop policy alternatives that can be used by development program implementation to minimize the problems that can be encountered in the implementation of village development program by the KPD.This research was done in Lompo Tengah and Pao-Pao Villages in the Regency of Barru in the Province of South Sulawesi. The research used purposive sampling, to analyse the contribution of the KPD on two villages, in which one of the villages has been successful and whereas in the other village it has not been successful. The study was based on a qualitative research method. Therefore, observation, and interviews, were among the approaches used in data collection.The findings of the study indicate the performance of the KPD was below the intended expectations because: (a) the recruited manpower of KPD which was done by the village head below the expected standard, (b) the village head could not understand the rational behind KPD, and he regarded KPD as just a burden upon him, (c) There is lack of technical development of the activities of KPD at the sub-regency level.There are four factors according to this study that influence the successful implementation of KPD in village development. These four factor are:factors are : bureaucratic motivation, the ability of KPD, LKMD (Village Resistance Institutional Support) leadership support, and community support. The various policy alternatives that can be recommended to overcome the problems that KPD faces in the village development are : first of all, it is to revitalise and strengthen the LKMD, secondly, it is to sustain KPD by providing it a special fund to activate its activities. This fund should be out of the village head control.